Occurrence of consonant production errors in liquid phonemes in children with operated cleft lip and palate - Prandini, Estefania Leite; Pegoraro-Krook, Maria Ines; Rillo Dutka, Jeniffer de Cassia; de Castro Marino, Viviane Cristina [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2011)
Information about the prevalence of consonant production errors, including compensatory articulations (CA), in individuals with cleft lip and palate (CLP) who speak Brazilian Portuguese is limited, particularly regarding liquid sounds. The literature primarily reports the occurrence of CA for plosive and fricative sounds, since occurrence of CAs in sounds that require higher amounts of oral air pressure is expected. While the use of CA during liquid sound production is not expected, clinical experience suggests that individuals with CLP present with inadequate backing, elevation, and anteriorization of the tongue as well as tongue clicks during production of /r/ and /l/. Objectives: Describe the occurrence of consonant error productions during liquid sounds for children with CLP; compare the occurrence between children operated with the Furlow and von Langenbeck techniques for palatoplasty; and compare the occurrence between children operated between 9-12 months and 15-18 months of age at primary palatoplasty. Material and Methods: A sample of 397 children (237 males and 160 females) with operated unilateral CLP was studied. In this group, 163 underwent palatoplasty with the Furlow procedure and 234 with the modified von Langenbeck procedure. Age at palatoplasty was between 9 and 12 months for 189 children and between 15 and 18 months for 208 children. Data about production of /l/, /r/, /R/, /lambda/ and consonant clusters /l/ and /r/ were obtained from speech pathology records. Speech pathologists registered the speech findings after an auditory-perceptual evaluation of the participants at the sixth year of age. Results: The use of middorsum palatal place (MDP) of production was identified for 2% of the sample. Tongue anteriorization of the /l/ production was observed for 55% of the children. No significant difference was found related to surgical technique, but children operated earlier developed the use of the consonant cluster In sooner than children operated later (p=0.040). Conclusion: We found a low occurrence of use of cleft related CA during attempts of production of liquid phonemes, and the variable age at primary palatoplasty significantly interfered with the acquisition of consonant cluster /r/.
Keywords: Articulation disorders; Cleft lip and palate; Liquid phonemes; Speech